EKSPLORASI KEMAMPUAN PESERTA DIDIK SEKOLAH DASAR DALAM MENULIS CERITA PENDEK MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM-CENTERED LEARNING (PCL) - Ayu, Yuni Faska; Kuntarto, Eko; Noviyanti, Silvina (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to identify students' ability in writing short stories after participating in learning with the Problem-Centered Learning (PCL) model, as well as to analyze the difficulties they face and the obstacles faced by teachers in implementing PCL. This study applied a qualitative case study approach at SDN 112/IX Muhajirin, involving 17 students  of fourth grade and one teacher. Data were collected through observation, assessment of student writing content, and interviews, then analyzed descriptively and thematically. The results showed that PCL had a positive impact on improving students' ability in writing short stories by developing clear themes, deep characters, and effective storylines. However, students faced difficulties in developing the author's background and adapting the language style. Teachers also faced challenges in technical readiness and institutional support. Based on these findings, it can be concluded that PCL is effective in improving elementary school students' short story writing skills despite facing implementation challenges. The need of additional support for the development of teaching strategies and in-depth training for teachers to overcome these difficulties is emphasized.